Structural features of multifidus muscle in patients with degenerative diseases of the lumbar spine - Radchenko, Volodymyr; Skidanov, Artem; Ashukina, Nataliya; Maltseva, Valentyna; Danyshchuk, Zinayda (ScienceRise: Medical Science, 2018)
Aim: to investigate the structural and functional changes in paravertebral muscles of patients with degenerative diseases of the lumbar spine based on histological and electron microscopic analyzes. Material and methods: histological and electron microscopic analysis of multifidus muscles of 49 patients (27 men and 22 women) was performed. Patients were on treatment between September 2015 and March 2018. The material was obtained during surgery for degenerative diseases of the lumbar spine: instability (9 patients), spondylolisthesis (11), spinal stenosis (9), lumbar disc herniation (20). Results: dystrophic disorders of muscle fibers were detected. There were thickness unevenness, discoid decay, loss of transverse striation and polygonality, replacement of muscle fibers with fat tissue, proliferation of fibrous tissue, edema. Prevalence of adipose tissue was found in 20 % of patients with a lumbar disc herniation, 22.22 % with instability, 36.36 % with spondylolisthesis, 44.44 % with spinal stenosis. The proliferation of connective tissue only in perimysium was defined in patients with a diagnosis "lumbar disc herniation", in others – both in perimysium and in endomysium. At the ultramicroscopic level, in the postoperative material of the patients with spondylolisthesis and spinal stenosis, in addition to intermyofibrillar edema and the violation of the architectonics of sarcomeres, as well as the structure and location of the mitochondria, focal necrosis of myofibrils were detected. Areas with a normal distribution of mitochondria were noted only in a group of patients with a lumbar disc herniation. In patients with a diagnosis of "spinal stenosis" violations of the ultrastructural organization of venules were found. This has a negative effect on nutrition and, accordingly, the functioning of a partitioned muscle. Conclusion: the greatest manifestations of dystrophic disorders of muscle fibers at the tissue and ultrastructural levels were revealed in patients with diagnoses of "spondylolisthesis" and "spinal stenosis"